2020
DOI: 10.1016/j.hrthm.2020.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Fatal arrhythmias: Another reason why doctors remain cautious about chloroquine/hydroxychloroquine for treating COVID-19

Abstract: BACKGROUND Early during the current coronavirus disease 19 (COVID-19) pandemic, hydroxychloroquine (HCQ) received a significant amount of attention as a potential antiviral treatment, such that it became one of the most commonly prescribed medications for COVID-19 patients. However, not only has the effectiveness of HCQ remained questionable, but mainly based on preclinical and a few small clinical studies, HCQ is known to be potentially arrhythmogenic, especially as a result of QT prolongation.OBJECTIVE The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…Chloroquine interacts with multiple cardiac ion channels including the human ether-a-go-go-related gene (hERG) potassium channel; a reduction in hERG channel potassium current is the main cause of acquired drug-induced long QT syndrome. Recent experimental data indicated that HCQ markedly increases the action potential dispersion and results in the development of repolarization alternans and initiates polymorphic VT [32] .…”
Section: Chloroquine / Hydroxychloroquinementioning
confidence: 99%
“…Chloroquine interacts with multiple cardiac ion channels including the human ether-a-go-go-related gene (hERG) potassium channel; a reduction in hERG channel potassium current is the main cause of acquired drug-induced long QT syndrome. Recent experimental data indicated that HCQ markedly increases the action potential dispersion and results in the development of repolarization alternans and initiates polymorphic VT [32] .…”
Section: Chloroquine / Hydroxychloroquinementioning
confidence: 99%
“…The intracellular face of the hERG channel is large and is lined with a number of aromatic residues allowing drugs like CQ and HCQ and others to bind this part of the channel and block the outward potassium current [36] , [37] . In a recent study using ex-vivo guinea pig and rabbit heart models, it was shown that HCQ resulted in the generation of repolarization alternans and precipitated polymorphic ventricular tachycardia [38] .…”
Section: Significant Cardiac Toxicity Concernsmentioning
confidence: 99%
“…In view of the inflammatory cytokine storm highly present in patients with severe COVID-19 causing acute lung injury, anti-inflammatory medications are proposed. Although several governments and international health authorities have promoted and encouraged the treatment with chloroquine/hydroxychloroquine ( 71 , 76 , 128 , 157 ), it must nonetheless be noted that these compounds present critical risk and benefit balance issues ( 44 , 185 , 216 ). In this context, recent clinical investigations have assessed promising alternatives, including chloroquine and its hydroxyl analog hydroxychloroquine, to evaluate whether they could prevent the virus from entering host cells, preclude viral replication, and dampen exacerbation of the immune response ( 44 , 182 , 185 , 216 ).…”
Section: Introductionmentioning
confidence: 99%